Lifelong Female Engagement in Sport: A Framework for Advancing Girls’ and Women’s Participation - Norm O'Reilly; Michelle Brunette; Cheri Bradish (Journal of Applied Sports Management, 2018)
In a collaborative and nationwide project, the authors examined the status and challenges of girls’ and women’s participation in sport in Canada through a comprehensive literature review, extensive secondary research, a representative survey with Canadian females, and a survey and consultations with leading female sport experts. This multi-level analysis led to the development of a framework for advancing girls’ and women’s participation in sport to guide stakeholders’ actions at the system, organization, and individual levels to improve the state of girls’ and women’s lifelong engagement in sport. Subscribe to JASM
Keywords: Barriers; female athletes; physical activity; sport participation; women